Formation of Nouns with Diminutive Meaning in Modern Karakalpak Language - Bekbergenova Gulaim Aizharykovna (Research Parks Publishing LLC, 2021)
The article deals with ways and forms of expressing subjective estimation of diminutive terms of nouns in modern Karakalpak. In spite of some works on this theme, it remains insufficiently explored in modern Karakalpak language.One of the forms of expressing subjective estimation of diminutive terms of nouns is affixation.This study presents the formation of diminutive affixes of nouns– sha/ - she, shaq/ - shek, -shyq/-shik ,-ek// -kin modern Karakalpak language. The paper first presents the characteristics of subjective evaluation and expressiveness of nouns. Next, the paper reviews the studies on subjective forms of the noun in Turkic linguistics. Then analysis of the diminutive suffixes of nouns in modernKarakalpak language is given,concluding that, diminutive forms in the Karakalpak language are expressed by means of diminutive affixes. These include the affixes-sha/ - she, - shak/ - shek, - shyk/ - shik, -ek /-k and give a diminutive meaning to a person, object, animal names, etc. and create a new form.